(untitled) (Jurnal Ampere, 2025)
The high demand for electrical energy in the industrial sector demands increased efficiency in utility systems, one of which is in boiler units. This study aims to analyze the effect of the Programmable Logic Controller (PLC)-based pressure and water level control system on the efficiency of electrical energy in two boiler units with a capacity of 10.5 tons/hour and 21 tons/hour at PT Indofood CBP Sukses Makmur Tbk Tanjung Api-Api. The research methods include boiler operational data collection, calculation of electrical energy consumption before and after PLC control logic optimization, and thermal efficiency analysis of the system. The results of the study show that the application of a PLC-based control system is able to maintain the stability of operating parameters according to the setpoint, improve reliability, and save electrical energy consumption. A 10.5-ton boiler has a saving of 108 kWh/day or 30%, while a 21-ton boiler has a saving of 72 kWh/day or 20%. The thermal efficiency of both boilers remained stable at the range of 70.16%, indicating that the increase in electrical efficiency did not decrease the thermal performance of the system. Thus, the use of PLCs has proven to be effective in improving electrical energy efficiency without interfering with boiler operation performance in industrial environments.